THE INFLUENCE OF ISLAMIC SHARIA ON THE CONSTITUTION OF THE REPUBLIC INDONESIA - Saenal Supandi; A.Muin Fahmal; Said Sampara (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal